Effects of males' presence on female behaviour during the rut - Djakovic, N.; Holand, Ø.; Hovland, A. L.; Weladji, R. B.; Roed, K. H.; Nieminen, M.
Females' dispersion during the mating season has been regarded as being determined primarily by the distribution of food resources. However, females' distribution and behaviour may also be affected by the males' availability during rut. Indeed, it is challenging to disentangle female dispersion for food from female mate choice. We present the results of female reindeer (Rangifer tarandus) behaviour in two manipulated herds during the peak week of the rut: one without males (MA) and one with males present (MP). Presence of males did not influence mean typical group size of females (MP herd: 10.14, MA herd: 11.85). However, females in the MA herd travelled longer daily distances (1.8km) compared to females in the MP herd (1.3km). The proportion of the time females spent feeding (~ 75%), walking (~ 16%), and standing (~ 8%) did not differ between the herds, whereas mating-related behaviour was, as expected, significantly higher in the MP herd, although it accounted for only 1.4% of their observed activity. The high proportion of time spent feeding indicates that females' movement is driven primarily by maximizing forage intake. No difference in the females' somatic body weight change during rut between the two herds indicates low cost of female mating related activities during rut. Contrary to our predictions, the results showed that female reindeer behaviour during the mating season is not affected by male availability, male mating or courtship behaviour, but is primarily driven by distribution of food resources. 2015